Synthesis and controlled release properties of anticancer drug nanodelivery systems based on protocatechuic and chlorogenic acids using layered hydroxide inorganic hosts - Barahuie, Farahnaz (2015)
Nanoscience and nanotechnology are the design, characterization, production, and application of structures by controlled manipulation of size and shape at the nano scale (1-100nm) that produces new materials with unique and superior properties compared to their counter regime parts. Anticancer drugs are used to treat malignancies or cancerous cell growths by preventing the development, maturation and proliferation of neoplasms. These drugs could destroy cancer cells but also have many side effects, because treatment destroys the body's normal cells in addition to cancerous cells. The use of nanotechnology in medicine or the so called nanomedicine has created new, safe and effective method of delivering anticancer drugs which releases the drug in predetermined time, reduces the undesired fluctuation of the drug levels in blood circulation, decreased duration therapy, improved patient compliance due to less frequent of drug administration, increases the drug solubility and reduces adverse side effects while enhanced therapeutic response. Layered hydroxides (LHs) are considered as promising new generation materials which can be used as hosts to construct organic-inorganic nanocomposites. These inorganic nanomaterials are composed of nanolayers with two-dimensional infinite layers similar to that of mineral brucite, Mg(OH)2 and offer wide applications in diverse areas. These inorganic nanolayer materials have extensively been used as unique delivery nanocarrier for anticancer drugs. In this study, protocatechuic acid (PA) and chlorogenic acid (CA) were intercalated into zinc layered hydroxide, magnesium-aluminium and zinc-aluminium layered double hydroxides in order to increase the therapeutic efficiency. Protocatechuic acid was intercalated into magnesium-aluminium-layered double hydroxide at Mg2+/Al3+ ratio of 4 (R=4) to form its nanocomposites and were synthesized by direct co-precipitation and ion exchange methods, labelled as PAND and PANE, respectively. This drug was also intercalated into zinc-aluminium-layered double hydroxide (R=2) to form its nanocomposites by direct method (PZAC) and nanocomposite by ion-exchange method (PZAE). Furthermore, protocatechuic acid was also intercalated into zinc layered hydroxide in order to obtain protocatechuic acid-zinc layered hydroxide nanocomposite (PAN). Chlorogenic acid was intercalated into magnesium-aluminium-layered double hydroxide (R=4) using direct co-precipitation and ion-exchange method for the formation of a nanocomposite by direct method (CMAC) and a nanocomposite by ion-exchange method (CMAE). This drug was also encapsulated into zinc-aluminium-layered double hydroxide (R=4) to form a nanocomposite using direct method (CZAC) and a nanocomposite using ion-exchange method (CZAE). Moreover, chlorogenic acid was also intercalated into zinc layered hydroxide to form chlorogenic acid-zinc layered hydroxide nanocomposite (CAN). All the nanocomposites exhibit the properties of mesoporous-type material, with greatly enhanced thermal stability of the intercalated drug compared to its free counterpart. X-ray diffraction pattern showed expansion of the basal spacing of the nanocomposites due to the monolayer arrangement of drug anions between the interlayer lamellae of the layered hydroxides. Furthermore, the FTIR result of nanocomposites corroborated the strong interaction between the guest and inorganic host in these nanocomposite materials. The release of drugs from the nanocomposites occurred slowly and in a sustained manner, so that it was 4000 (83%), 7500 (59%), 6706 (79%), 8612 (86%), 7001 (87%), 7088 (79%), 5141 (78%), 11470 ( 88%), 6610 ( 75 %) and 9660 (99%) minutes at pH 7.4 compared to 900 (98%), 1000 (85%), 2391 (91%), 3068 (98%), 1592 (95%), 3855 (93%), 3044 (89%), 1435 (99%), 1350 (97%), 4800 (88%) minutes at pH 4.8 from PAND, PANE, PZAC, PZAE, PAN, CMAC, CMAE, CZAC, CZAE and CAN nanocomposites, respectively, indicating that the nanocomposites are potential drug controlled release formulations. In vitro cytotoxicity assay studies showed that PAND and PANE nanocomposites had greater suppression effect on human breast cancer (MCF-7) and human cervical cancer (HeLa) cell lines compared to free protocatechuic acid, without toxicity on 3T3 normal fibroblust cell after 72 hours incubation. In addition, the cell viability test of magnesium-aluminium-layered double hydroxide indicated the absence of toxicity toward normal fibroblast (3T3) cells and both cancer cell lines. PZAE and PZAC nanocomposites exhibit better cytotoxicity effect than the free PA in human cervical (HeLa), colorectal (HT29) and human liver (HepG2) cancer cells. However, they did not show cytotoxicity in 3T3 normal fibroblast cells, after 72 hours treatment. The anticancer activity of PZAE and PZAC was more extensive particularly in HepG2 and HT29 cancer cell lines. In addition, increasing of zinc-aluminium-layered double hydroxide (R=2) concentration lead to killing the 3T3 normal fibroblast and cancer cells. The inhibition of cancer cell growth in cervical adenocarcinoma (HeLa), liver hepatocarcinoma (HepG2) and colorectal adenocarcinoma (HT29) cancer cells was higher for the PAN nanocomposite than for free protocatechuic acid. In this work, the tumor growth suppression of PAN was more prominent in HT29 and HepG2 cell lines. Furthermore, the high concentration exposure of zinc oxide suppressed cell growth in 3T3 normal fibroblast and cancer cell lines. The nanocomposites, CMAE and CMAC, showed better cytotoxicity properties against various human cancer cells namely human breast (MCF-7), human cervical (HeLa) and human lung (A549) cancer cells particularly the liver cancer cells (HepG2) in a dose-dependent manner, compared to free chlorogenic acid. In addition, these nanocomposites did not produce any toxicity behavior in normal fibroblast cells. CZAE and CZAC nanocomposites possess significant anti-tumor properties in cervical, HeLa and breast, MCF-7 cancer cells particularly liver cancer, HepG2 and lung cancer, A549 cells in a dose-dependent manner compared to chlorogenic acid without showing any toxicity on normal fibroblast cells. In addition, the CZAC exerted better cytotoxic effects than the CZAE compound, particularly in liver cancer cells. However, there was no inhibition in cell proliferation of normal fibroblast and cancerous cells when they were exposed to zinc-aluminium-layered double hydroxide (R=4). CAN nanocomposite indicates an increased in cytotoxicity compared to the free form of chlorogenic acid in MCF-7 and HepG2 cancer cell lines tested, particularly in HepG2 liver cancer cell lines in a dose-dependent manner without a toxic effect on normal fibroblast, HeLa and A549 cancer cells. In essence, all nanocomposites showed the sustained release properties and can therefore be used as controlled-release formulations and the introduction of zinc layered hydroxide, magnesium-aluminium and zinc-aluminium layered double hydroxides layers in protocatechuic and chlorogenic acid improved the anticancer efficacy and selectivity feature of the compounds. All the works presented in the thesis have been published in the journals of the international repute, which reflect the quality of this research work.